(untitled) (Semiárida, 2020)
The Livestock National Market of Liniers concentrates about 50 % of the pigs traded in the country and acts as a price fixer. Great seasonal variations in prices are noted, and periodically there is a cycle (4 to 6 years) with oversupply and an abrupt drop of prices or vice versa. The results of sending pigs ready f6r slaughtering to market with different alternatives of selling periods: monthly, bimonthly and half-yearly, were analyzed for a twenty-five year’s period, and different options that each alternative may bring. The pig-corn relation was taken as a reference point. As a conclusion no important advantages were found for any of the considered alternatives although there is a slight improvement with the half-yearly shipments. These ones will surely decrease due to higher financial costs.